Pendeteksian Kecurangan Laporan Keuangan Dengan Beneish Model - Dwi Sasongko; Didit Supriyadi; Kosasih Kosasih (Entrepreneurship Faculty, Universitas Garut, 2022)
The phenomenon of fraud in the delivery of fraudulent financial statements sometimes still occurs in a company. Using the Beneish Model can detect fraudulent financial statements. This study aims to determne the percentage of companies including Manipulators, Non Manipulators, and Gray Company. The research.methodology used in this study is.quantitative. The data that researchers use are secondary data obtained from www.idx.co.id. The population used in this study are all mining companie listed on the Indonesia Stock Exchage in the period 2013-2017, with a sample of 15 companies. Data analysis using Beneish Model. The variables in this study are Days Sales.in Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI) , Sales Growth Index (SGI) , and Total Accrual to Total Assets (TATA). The results showed that the percentage of manipulators companies was 6.6% in 2013, 0% in 2014, 13.3% in 2015, 6.6% in 2016, and 6.6% in 2017, non manipulators in 80% in 2013, 66.6% in 2014, 66.6% in 2015 53.3% in 2016, 46.6% in 2017, gray company 13.3% in 2013, 33.3% in 2014, 20% in 2015, 40% in 2016, 46.6% in 2017. Fenomena kecurangan dalam penyampaian laporan keuangan yang curang terkadang masih saja terjadi pada suatu perusahaan. Menggunakan Model Beneish dapat mendeteksi kecurangan laporan keuangan. Penelitian ini bertujuan untuk mengetahui persentase perusahaan yang meliputi Manipulator, Non Manipulator, dan Grey Company. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif. Data yang peneliti gunakan adalah data sekunder yang diperoleh dari www.idx.co.id. Populasi yang digunakan dalam penelitian ini adalah seluruh perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia periode 2013-2017, dengan sampel sebanyak 15 perusahaan. Analisis data menggunakan Model Beneish. Variabel dalam penelitian ini adalah Days Sales.in Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), dan Total Accrual to Total Assets (TATA). Hasil penelitian menunjukkan bahwa persentase perusahaan manipulator sebesar 6,6% pada tahun 2013, 0% pada tahun 2014, 13,3% pada tahun 2015, 6,6% pada tahun 2016, dan 6,6% pada tahun 2017, nonmanipulator sebesar 80% pada tahun 2013, 66,6% pada tahun 2014, 66,6 % pada 2015 53,3% pada 2016, 46,6% pada 2017, perusahaan abu-abu 13,3% pada 2013, 33,3% pada 2014, 20% pada 2015, 40% pada 2016, 46,6% pada 2017.